Manutenção do potencial doador de orgãos pela equipe multiprofissional e a inserção da família neste contexto - (:unkn) unknown (Universidade Federal do Pampa, 2017)
To know the perspectives of health professionals in relation to the process of maintenance of the potential organ donor and the insertion of the family in this context. Method: Qualitative, descriptive and exploratory field research carried out at a hospital large, with a multidisciplinary team that works to maintain the potential donor. There were a total of nine participants, these being linked to the nursing professions, medicine, physiotherapy, psychology and nursing technician. For data collection, we used the focus group technique, with three meetings for data production. The same underwent thematic analysis. Results: Two categories were established thematic areas: “Perspectives regarding the organization of the multidisciplinary team to maintenance of the potential donor ", and" Communication for the insertion of the family in the context of maintenance of the potential donor ”. The multiprofessional team centralizes decisions and behaviors in the doctor, and nursing works to solve the demands caused by service gaps, or by other professionals. However, there is perception part of the professionals that there is no cohesion among the team regarding the management of potential organ donor. The physiotherapist and psychologist are still professionals distanced in the maintenance of the patient in brain death. Conclusion: From the data of this study, it is possible to realize the need to build and implement education protocols with a view to being applied by CIHDOT teams to health professionals that work in assisting the potential donor, to better conduct the process of maintenance and communication with family members.
Maintenance of the potential organ donor by the multiprofessional team and the insertion of the family in this context
Keywords: Morte efálica; Unidade de Terapia Intensiva; Equipe de assistência ao paciente; Tratamento com preservação do órgão; Obtenção de tecidos e órgãos; Enfermagem; Brain Death; Intensive care unit; Customer service team patient; Treatment with organ preservation; Procurement of tissues and organs; Nursing; UTI; Urgência e emergência; Doação de órgãos; Saúde da família; CNPQ::CIENCIAS DA SAUDE